Analysis of Natural Convection Flow in a Trapezoidal Cavity Containing a Rectangular Heated Body in Presence of External Oriented Magnetic Field - Akter, A.; Parvin, S. (Journal of Scientific Research, 2018)
The laminar natural convection flow and heat transfer inside a trapezoidal cavity filled with air and containing a rectangular block is investigated numerically. The left and right walls of the cavity are cold, the top and bottom walls are adiabatic and the rectangular body is heated uniformly. Finite Element Method of Galerkin’s weighted residual scheme is used to solve the transport equations with appropriate boundary conditions. The main objective of this study is to explore the influence of pertinent parameters such as Rayleigh number, Hartmann number and orientation of the magnetic field on the flow and heat transfer performance of the fluid while the Prandtl number is considered fixed. Results indicate that the heat transfer rate is significantly affected by increasing the mentioned parameters.